'We are willing, but we have challenges': Qualitative enquiry on midwives' views on factors influencing the prevention of mother-to-child transmission of hepatitis B program - Adiza Mumuni Atoko RM, MPHIL; Florence Naab RM, PhD; Charles Ampong Adjei RN, PhD; Vivian Efua Senoo-Dogbey RN, PhD (SAGE Publishing, 2024)
Introduction Mother-to-child transmission of hepatitis B infection is one of the major routes of hepatitis B virus (HBV) infection in Africa. Amusingly, Africa is the only region yet to meet the World Health Organization's target of reducing the prevalence of HBV infection to less than 1% among children under 5 years of age by 2020. In Ghana, little has been documented about midwives' views on the factors impacting the successful implementation of mother-to-child transmission via HBV prevention programs. Objective This study explored midwives' views on the challenges associated with the prevention of mother-to-child transmission of HBV infection in the La-Nkwantanang municipality. Methods The study adopted an exploratory descriptive qualitative design and involved 14 midwives who were purposively recruited from a primary-level health facility in the La-Nkwantanang Municipality, Accra. Individual face-to-face interviews were conducted using an in-depth interview guide. The data were content analyzed using the six steps recommended by Braun and Clark. Results Three main themes, namely, health professional or midwife factors and patient and health facility factors, negatively impacted the prevention of maternal-to-child transmission program. The five subthemes identified in this study included lack of awareness, financial constraints, and unavailability of logistics and protocols. The study recognized that midwives face many challenges even though they have a strong desire to prevent vertical transmission of HBV. Conclusion The implementation of a mother-to-child transmission program is negatively impacted by many intrinsic, client, and health facility factors. Midwives who act as major stakeholders need to be periodically trained on the components and protocols for managing pregnant women living with HBV. The necessary logistics and management protocols need to be urgently provided. The skills and education obtained from the training will empower midwives to be knowledgeable about how to deliver quality care and provide education and support for HBV-infected pregnant women. The provision of logistics needed for the successful implementation of the program could avert delays associated with the administration of the hepatitis B birth dose vaccine and immunoglobulin to exposed newborns.